An integrated microfluidic platform for nucleic acid testing - Sun, Antao; Vopařilová, Petra; Liu, Xiaocheng; Kou, Bingqian; Řezníček, Tomáš; Lednický, Tomáš; Ni, Sheng; Kudr, Jiří; Zítka, Ondřej; Fohlerová, Zdenka; Pajer, Petr; Zhang, Haoqing; et al. (Microsystems & nanoengineering, 2024)
This study presents a rapid and versatile low-cost sample-to-answer system for SARS-CoV-2 diagnostics. The system integrates the extraction and purification of nucleic acids, followed by amplification via either reverse transcription-quantitative polymerase chain reaction (RT-qPCR) or reverse transcription loop-mediated isothermal amplification (RT-LAMP). By meeting diverse diagnostic and reagent needs, the platform yields testing results that closely align with those of commercial RT-LAMP and RT‒qPCR systems. Notable advantages of our system include its speed and cost-effectiveness. The assay is completed within 28 min, including sample loading (5 min), ribonucleic acid (RNA) extraction (3 min), and RT-LAMP (20 min). The cost of each assay is ≈ $9.5, and this pricing is competitive against that of Food and Drug Administration (FDA)-approved commercial alternatives. Although some RNA loss during on-chip extraction is observed, the platform maintains a potential limit of detection lower than 297 copies. Portability makes the system particularly useful in environments where centralized laboratories are either unavailable or inconveniently located. Another key feature is the platform's versatility, allowing users to choose between RT‒qPCR or RT‒LAMP tests based on specific requirements.
Keywords: Electrical and electronic engineering; Chemistry; Microfluidics